Sistem Pakar Diagnosa Penyakit Hipotermia Menggunakan Metode Certainty Factor - Sindi Feliza Dianti; Suendri (APIC, 2023)
Abstract— Information technology that is currently developing is utilized in various fields such as education, health and others. One of them is hypothermia in infants. Hypothermia is a condition when the baby's temperature is below normal. It is also not uncommon for someone who sees their child to have some symptoms to seek information about the disease their child is suffering from from people around them or the internet media. When a person is suspicious of a child suffering from hypothermia, then that person needs to confirm the illness his child is suffering from. So that someone who wants to make sure the disease suffered by his child tends to go to the doctor. The problems that occur are costs and places far from home. The purpose of this research was to apply the Certainty Factor method to diagnose hypothermia and to make an expert system application for diagnosing hypothermia using the Certainty Factor approach. The results of the level of confidence based on the symptoms found from hypothermia were obtained using the Certainty Factor method, which was 96.08%. With this system, it is hoped that it will help parents determine the disease their child is suffering from, namely Hypothermia without having to see a doctor for initial treatment.